What is in a look? The accountability of gaze in trajectories to conflict - Clift, Rebecca (Frontiers in Psychology, 2024)
This study investigates the role of gaze in initiating episodes of conflict by examining, using multimodal conversation analysis, a set of cases in which a recipient is prompted to speak by another’s extended gaze. In these cases, this recipient response may be, e.g., “What,” or a more elaborate demand for an account, such as “Why are you looking at me like that for?” Here we investigate the characteristics of the gaze that prompts such responses, and what actions such responses constitute. While “What” compositionally resembles other-initiated repair, its sequential position characterizes it as a so-called “go-ahead” action. In these cases, the sequential positioning of such gazes, constituting it structurally as a so-called “pre,” alongside its durational characteristics and facial expression, are examined to identify the normative associations of gaze and subsequent conduct that make such gazes accountable.